A VALIDATED RP-HPLC METHOD FOR IMPURITY PROFILING OF SODIUM NITROPRUSSIDE IN INJECTION DOSAGE FORM - P., MURALI KRISHNAM RAJU; B., VENKATA NARAYANA; P., SHYAMALA; KONDRA, SRINIVASU; DANTULURI, HSN RAJU (International Journal of Applied Pharmaceutics, 2021)
Objective: The main objective of this research work is to develop and validate a single reverse-phase high-performance liquid chromatography (RP-HPLC) method. This method should becapable of quantifying all the known, as well as other possible degradation impurities of sodium nitroprusside (SNP) in its injection formulation. Methods: Of allmethod development trails, we have observed better separations between known and degradation impuritiesin Inert sustain C18, (250 x 4.6) mm, 5 µm column at 30 °C temperature. Isocratic elution was carried out by using pH 8.6 phosphate buffer and acetonitrile in the ratio of 65:35 %v/v with a flow rate of 0.8 ml/min. The detection was carried out at 220 nm, with an injection volume of 10 µl. Results: In the proposed method, SNP was eluted at 22.5 min. Nitrite, nitrate, and ferrocyanide were linear from 0.25 to 37 μg/ml, ferricyanide was linear from 1.0 to 37 μg/ml, and SNP was linear from 0.75 to 37 μg/ml. The % RSD for six spiked samples (precision)was found to be less than 0.5 %. Accuracy was performed for known impurities from LOQ to 150 % for a 0.5 % specification level. The resultswere found to be in the acceptance range of 90-110 %. The LOQ concentration of nitrite, nitrate, and ferrocyanide was 0.25 μg/ml each,LOQ offerricyanide and SNP was found to be 1.0 μg/ml and 0.75 μg/ml, respectively. The SNP injection samples were exposed to different degradation conditions, and the results were found specific in the proposed methodology. Conclusion: The proposed RP-HPLC method is specific, precise, accurate, linear, stable, and robust for quantification of known and other possible degradation impurities in SNP injection formulation.